A monostatic laser polarization isolation system for light pollution and velocity combined laser heterodyne detection. Issue 1 (27th September 2021) - Qu, Yang; Jia, Xue; Chen, Zhongbiao
Abstract: In order to solve the signal aliasing problem when tracking and detecting mobile laser pollution sources, a monostatic laser polarization isolation system is designed and built. Through the polarization state and received power detection experiments, the results of the prototype show that this system can effectively separate different signal echoes and has excellent signal receiving ability.